Hollow MgNi1.4Zn0.6/CaCu2.79Fe4.21O12 nanocomposite synthesis via ultrasonic high‐temperature spray pyrolysis. Issue 9 (25th April 2018) - Karunakaran, Gopalu; Jagathambal, Matheswaran; Kumar, Govindan Suresh; Venkatesh, Manickam; Kolesnikov, Evgeny; Kuznetsov, Denis
Abstract: In this study, a distinctive hollow MgNi1.4 Zn0.6 /CaCu2.79 Fe4.21 O12 nanocomposite was synthesized for the first time using ultrasonic high‐temperature spray pyrolysis method controlled at 1200°C. Effect of various concentrations (0.01, 0.1, and 1 mol L −1 ) of the precursor solution on particle size and crystalline phase of nanocomposites was also analyzed. XRD and SEM results confirmed the difference in the particle size and crystalline pattern of the synthesized nanocomposite arisen due to the difference in concentrations. The results of antibacterial and antioxidant studies showed that the nanocomposites possessed remarkable antibacterial and antioxidant activities. Thus, the prepared hollow MgNi1.4 Zn0.6 /CaCu2.79 Fe4.21 O12 metal oxide nanocomposite via ultrasonic high‐temperature spray pyrolysis can be an excellent material in various biomedical applications. Abstract : Hollow MgNi1.4 Zn0.6 /CaCu2.79 Fe4.21 O12 nanocomposite synthesis via ultrasonic spray pyrolysis with promising antibacterial and antioxidant activities for different healthcare applications.